2002
DOI: 10.1095/biolreprod.102.006395
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis of Capacitated Rabbit Spermatozoa to Follicular Fluid Revealed by a Novel Directionality-Based Assay1

Abstract: Precontact communication between gametes is established by chemotaxis. Sperm chemotaxis toward factor(s) in follicular fluid (FF) has been demonstrated in humans and mice. In humans, the chemotactic responsiveness is restricted to capacitated spermatozoa. Here, we investigated whether sperm chemotaxis to factor(s) present in FF also occurs in rabbits and, if so, whether only capacitated spermatozoa are chemotactically responsive. Chemotaxis assays were performed by videomicroscopy in a Zigmond chamber. We meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
119
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(127 citation statements)
references
References 29 publications
8
119
0
Order By: Relevance
“…The sperm showed the strongest chemotaxis toward 10 3 ‐ or 10 4 ‐fold‐diluted (0.1% or 0.01%) follicular fluid 10, 11. In this study, the responsiveness of bull sperm to the BFF at the different concentrations of between 0.01% and 100% was compared and it was found that 0.1% BFF elicited the strongest response.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The sperm showed the strongest chemotaxis toward 10 3 ‐ or 10 4 ‐fold‐diluted (0.1% or 0.01%) follicular fluid 10, 11. In this study, the responsiveness of bull sperm to the BFF at the different concentrations of between 0.01% and 100% was compared and it was found that 0.1% BFF elicited the strongest response.…”
Section: Discussionmentioning
confidence: 87%
“…In the human,16, 21, 22, 23 rabbit,10 and mouse,15 sperm chemotaxis to the follicular fluid and egg‐related material has been observed, but the mechanism of sperm chemotaxis is not sufficiently understood. In this study, it was investigated whether bull sperm can be attracted to the BFF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4] Follicular fluid, oviductal fluid and the conditioned medium of the egg-cumulus complex are biological sources of chemoattractants. [3][4][5][6][7][8][9][10][11] Follicular fluid that has been obtained from one species may attract spermatozoa of other species, suggesting that chemotaxis may not be a species-specific phenomenon. 12 A small quantity of progesterone, which is secreted by the cells surrounding the egg, is able to attract spermatozoa.…”
Section: Introductionmentioning
confidence: 99%